Analisis Lembar Kerja Siswa Praktikum Fotosintesis Dengan Uji SACHS: Students Work Sheet Analysis Of Photosynthesis Practicum With SACHS Test - Fidya afiyatusyifa; Sri Anggraeni; Bambang Supriatno (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
This study aims to analyze and find out the effectiveness of Student’s Worksheet (LKS) in the Photosynthesis practicum with Sachs test experiments and taken from biology books for junior and senior high school, 5 LKS consisting of 2 LKS Junior High School and 3 LKS Senior High School which are used as a source of learning and published by several well-known publishers. The method used in this study is a qualitative description with the sampling technique used is purposive sampling. Based on the findings in the field, it was found that there were still problems in several components in the photosynthetic LKS practicum with the Sachs test. The results obtained show that for notes / transformations, the percentage of scores obtained in junior and senior high school worksheets has not yet shown an ideal score (score 0), which means no notes or transformations can be identified. If practicum does not occur in the process of recording and transformation of data, the claims of knowledge made can be wrong or irrelevant to the conceptual side of Diagram Vee. Abstrak. Penelitian ini bertujuan untuk menganalisis dan mengetahui efektivitas penggunaan Lembar Kerja Siwa (LKS) pada praktikum Fotosintesis dengan percobaan uji Sachs dan diambil dari buku biologi untuk SMP dan SMA/MA sebanyak 5 LKS yang terdiri dari 2 LKS SMP dan 3 LKS SMA yang dijadikan sebagai sumber belajar dan dipublikasi oleh beberpa penerbit ternama. Metode yang digunakan dalam penelitian ini adalah deskripti kualitatif dengan teknik sampling yang digunakan yaitu purposive sampling. Berdasarkan hasil temuan dilapangan ditemukan bahwa masih terdapat permasalahan pada beberapa komponen dalam LKS praktikum fotosintesis dengan percobaaan uji Sachs. Hasil yang diperoleh menunjukan bahwa Untuk catatan/transformasi, persentase perolehan skor pada LKS SMP dan SMA belum menunjukkan skor ideal (skor 0) yang artinya tidak ada catatan atau transformasi yang dapat diidentifikasi. Jika pada praktikum tidak terjadi proses pencatatan dan transformasi data, maka klaim pengetahuan yang dilakukan bisa menjadi salah atau tidak relevan dengan sisi konseptual Diagram Vee.